Peptide Cyclization at High Concentration - Wills, Rachel D.; Adebomi, Victor T.; Raj, Monika (Synlett, 2020)
The emergence of cyclic peptides as pharmaceuticals has led to an eruption of new methodologies for macrocyclization. However, the cyclization of peptides at high concentrations presents a challenge due to the production of side products like dimers and oligomers. This factor is more pronounced with the cyclization of peptides composed of fewer than seven amino acids, thus has created a need for a new synthetic strategy. Herein, we will elucidate a new chemoselective method termed ‘CyClick’ that works in an exclusively intramolecular fashion preventing the formation of commonly occurring side products such as dimers and oligomers, even at relatively high concentration.1 Introduction2 Known Methodologies3 Novel CyClick Chemistry4 Conclusion and Outlook
Keywords: peptides; macrocycles; high concentration; oligomerization; CyClick chemistry; stereoselectivity